Yoga como uma proposta para melhora dos sintomas do climatério em mulheres na pós-menopausa com queixa de insônia - Afonso, Rui Ferreira [UNIFESP] (2011)
Introduction: The practice of Yoga has proven to have positive effects on the reduction of insomnia. Studies also show its effects on the reduction of climacteric symptoms. However, no studies have been carried out so far that evaluated the effects of Yoga on postmenopausal women with a diagnosis of insomnia. Objective: to evaluate the effect of Yoga practice on the physical and mental health of postmenopausal women with a diagnosis of insomnia, as well as on their climacteric symptoms. Methods: Postmenopausal women without hormonal therapy, 50 to 65 years old, with apnea-hypopnea index <15 and a diagnosis of insomnia, were randomly assigned to three groups: control, passive stretching, and Yoga. Questionnaires were applied before and four months after intervention to evaluate quality of life; symptoms of anxiety and depression; climacteric symptomatology; severity of insomnia; daytime sleepiness and stress. Volunteers also underwent polysomnography. The study lasted four months. Results: There were 44 volunteers at the end of the study. When compared to the Control group, the Yoga group presented significantly lower scores for climacteric symptomatology and insomnia severity, and better scores in quality of life and resistance phase of stress after treatment. The reduction in the severity of insomnia in the Yoga group was significantly higher than in the control group and passive stretching groups. Conclusion: This study showed that a specific sequence of Yoga might be effective to reduce insomnia and menopause symptoms, and improve quality of life in postmenopausal women with insomnia.